Retinoblastoma update – therapy (part II) - Pogrzebielski, Arkadiusz; Shields, Carol; Romanowska-Dixon, Bożena; Shields, Jerry (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The aim of this paper is to present updated data on the treatment of retinoblastoma. The authors describe current management based on the International Intraocular Retinoblastoma Classification (IIRC). They discuss the different methods of treatment, including chemoreduction, subconjunctival carboplatin, transpupillar thermotherapy, cryotherapy, laser photocoagulation, episcleral plaque radiotherapy, external-beem radiotherapy and enucleation.